The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1051/0004-6361/201117466
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity gradients in disks

Abstract: Aims. We examine radial and vertical metallicity gradients using a suite of disk galaxy hydrodynamical simulations, supplemented with two classic chemical evolution approaches. We determine the rate of change of gradient slope and reconcile the differences existing between extant models and observations within the canonical "inside-out" disk growth paradigm. Methods. A suite of 25 cosmological disks is used to examine the evolution of metallicity gradients; this consists of 19 galaxies selected from the RaDES … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
223
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(268 citation statements)
references
References 73 publications
40
223
1
Order By: Relevance
“…From a MWG-like model, we obtained the evolution of the radial gradient of Oxygen abundances, finding a gradient of ∼ −0.2 dex kpc −1 for z = 2 which flattens with time until reaching the present time value ∼ −0.05 − 0.06 dex kpc −1 . This behavior was in agreement with the cosmological simulations from Pilkington et al (2012) and also with the Yuan et al (2011) value found at z ∼ 1.5. However, it is necessary to take into account that this gradient was calculated with the O abundances of all radial regions † Recent works conclude that there are at least two stellar generations in these old objects.…”
Section: Introductionsupporting
confidence: 91%
“…From a MWG-like model, we obtained the evolution of the radial gradient of Oxygen abundances, finding a gradient of ∼ −0.2 dex kpc −1 for z = 2 which flattens with time until reaching the present time value ∼ −0.05 − 0.06 dex kpc −1 . This behavior was in agreement with the cosmological simulations from Pilkington et al (2012) and also with the Yuan et al (2011) value found at z ∼ 1.5. However, it is necessary to take into account that this gradient was calculated with the O abundances of all radial regions † Recent works conclude that there are at least two stellar generations in these old objects.…”
Section: Introductionsupporting
confidence: 91%
“…This assumption is a natural outcome of the mass, momentum, and energy conservation laws imposed in the simulations of disks in a cosmological context (Brook et al 2011(Brook et al , 2012Few et al 2012;Pilkington et al 2012a,b;Gibson et al 2013). Pilkington et al (2012a) examined a set of 25 simulations, from several groups, using different codes and initial conditions (Stinson et al 2010;Rahimi et al 2011;Kobayashi & Nakasato 2011;Few et al 2012) to predict the present-day metallicity gradient in MW-like galaxies and its evolution. Although the evolution of the simulated metallicity gradients depends strongly on the choice of the subgrid physics employed, most of the simulated galaxies tend to a similar present-day gradient of ∼−0.05 dex kpc −1 , in agreement with the Chiappini et al (2001) and Mollá & Díaz (2005) models for normal galaxies as the MW.…”
Section: Theoretical Predictions From Cosmological Simulationsmentioning
confidence: 99%
“…Recently, a new set of cosmological hydrodynamic simulations have started to predict how the spatially resolved information of the properties of stellar populations in galaxies can constrain the complex interplay between gas infall, outflows, stellar migration, radial gas flows, and star formation efficiency, in driving the inside-out growth of galactic disks (Brook et al 2012;Gibson et al 2013;Few et al 2012;Pilkington et al 2012a;Minchev et al 2014). Radiative cooling, star formation, feedback from supernovae, and chemical enrichment are also included in simulations to predict radial metallicity gradients as a function of merging history.…”
Section: Introductionmentioning
confidence: 99%
“…However, a similarly lower [Fe/H] could also be expected if the Head was a remote part of an progenitor disk involving the Body -stellar metallicity gradient determinations (e.g. Pilkington et al 2012;Sánchez-Blázquez et al 2014) are quite noisy, however, and moreover, in that case the Tail would be expected to have a similar lower value, which it does not have.…”
Section: Two or Three Galaxies?mentioning
confidence: 92%